The Value of a Loss: The Impact of Restricting Tax Loss Transfers - BÜHRLE, THERESA; CASI, ELISA; STAGE, BARBARA; VOGET, JOHANNES (Journal of Accounting Research, 2026)
ABSTRACT We study the economic consequences of anti‐loss trafficking rules, which disallow the use of loss carryforwards as a tax shield after a substantial ownership change. We use staggered changes to these rules in the EU27 Member States, Norway, and the United Kingdom from 1998 to 2019 and find that limiting the transfer of tax losses is related to the number of mergers and acquisitions (M&A) declining by 18%, driven by loss‐making targets. Turning to broader industry dynamics, we find decreases in survival rates of young companies after tighter regulations. Loosening of regulation is associated with increased firm survival. Tightening (loosening) anti‐loss trafficking rules is related to decreased (increased) industry productivity, especially in R&D‐intensive industries that are more prone to loss‐making. Finally, tighter anti‐loss trafficking rules are associated with lower deal synergies and risk‐taking. All effects concentrate in strict regimes.